Regional Finance And Employment Dynamics: An Empirical Study Based On Secondary Data In Indonesia - Maryanti, Sri; Widayat, Prama; Lubis, Nurhayani; Murni, Yanti (ADPEBI International Journal of Business and Social Science, 2024)
This study examines the impact of regional financial management on employment dynamics in Indonesia using secondary data from 2019 to 2023. This study focuses on three main components of finance, namely Regional Original Revenue, Balance Fund, and Regional Expenditure, and analyzes their effects on employment indicators such as the Open Unemployment Rate and the Labor Force Participation Rate. The results show that although these financial variables have a high correlation with labor market outcomes, the individual effects of these variables are often not statistically significant, indicating challenges in the effectiveness of current fiscal policies in reducing unemployment and increasing labor force participation. Problems such as multicollinearity and autocorrelation are identified, so better financial management strategies are needed This research study investigates how regional financial management affects employment dynamics in Indonesia, using data from 2019 to 2023. The study focuses on three main financial components: Regional Original Revenue, Balance Fund, and Regional Expenditure, and analyzes their impact on employment indicators such as the Open Unemployment Rate and the Labor Force Participation Rate. The results indicate that while these financial variables correlate highly with labor market outcomes, their individual effects are often not statistically significant. This suggests challenges in the effectiveness of current fiscal policies in reducing unemployment and increasing labor force participation. The study identifies issues such as multicollinearity and autocorrelation, highlighting the need for improved financial management strategies to align with employment goals. It emphasizes the importance of policy reforms to optimize the role of regional finance in promoting inclusive employment growth, particularly in response to Indonesia's unique economic structure and post-pandemic challenges. This research contributes to existing literature by providing empirical insights into the direct relationship between fiscal decentralization and labor market performance in developing countries. Align with employment goals. This research highlights the importance of policy reforms to optimize the role of regional finance in encouraging inclusive employment growth, especially in response to Indonesia's unique economic structure and post-pandemic challenges. This research contributes to the existing literature by offering empirical insights into the direct relationship between fiscal decentralization and labor market performance in developing countries..